The THE INFLUENCE OF BRAIN GYMNASTIC TO LEARNING ACHIEVEMENT ON STUDENTS IN MOJOKERTO REGENCY - Tri Ratna Ningsih; SITI INDATUL LAILI; Tri Peni (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2019)
Memory is used for building self-reliance and self-confidence in children. Memory disorders will complicate learning process and cause health problems for children. Exercise activities will familiarize children to maintain the main cognitive function of the brain and can help them to achieve achievement. This study aims to determine the influence of brain gymnastic to learning achievement on Al-Akbar Islamic Elementary School students Mojokerto. This research was done with quasi-experiment method with "Pretest-Postest with Control Group Design" in Islamic Elementary School of Al-Akbar Mojokerto. The sample was determined purposively, with 50 students. Brain gymnastic was done 6 times a week for 4 weeks with 7-10 minutes in each exercise, while the child's learning achievement was measured by the test score. The instruments in the study used observational data on brain exercise and reports on children's learning achievement Data were analyzed by using Wilcoxon Mann Whitney test with SPSS for Windows. The results showed that learning achievement before brain gymnastics was mostly satisfying amounted to 32 respondents (97%) in treatment group and for control group were mostly very satisfying amounted to 9 respondents (28%) in. The learning achievement after brain exercises for 4 weeks was mostly very satisfying 29 respondents (88 %) in treatment group, while in control group, almost half respondents were rated satisfying amounted to 16 respondents (49%). Data result with Man Witney got p value 0,008, meant there was influence of brain gymnastics in improving learning achievement. By doing simple movement has already activate brain cells and increase blood flow to the brain so student can receive knowledge that provided by teachers and increase learning concentration.